2004
DOI: 10.1097/00004347-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunohistochemical Analysis of Granulosa and Sertoli Components in Ovarian Sex Cord-Stromal Tumors with Mixed Differentiation: Potential Implications for Derivation of Sertoli Differentiation in Ovarian Tumors

Abstract: Granulosa cell tumors of the ovary occasionally show admixed Sertoli components, just as tumors that are predominantly Sertoli or Sertoli-Leydig cell tumors can contain minor granulosa elements. Although the immunoprofiles of pure granulosa cell tumors and pure Sertoli cell tumors have been characterized, little is known regarding what immunophenotypic relationships exist between the granulosa and Sertoli components in ovarian sex cord-stromal tumors that contain both elements. Furthermore, it is not completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…Immunohistochemical markers used for this purpose involve PANCK, LMWCK (CK8/18), CK7, ER, PR, EMA of which positivity were in favour of endometrioid carcinoma and inhibin , calretinin, WT-1 to show sex cord lineage (4,5,15,(17)(18)(19). Inhibin  and calretinin are highly sensitive and specific markers to show sex cord lineage, being expressed in 82% to 98% and 50% to 60% of ovarian pure Sertoli cell tumors (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical markers used for this purpose involve PANCK, LMWCK (CK8/18), CK7, ER, PR, EMA of which positivity were in favour of endometrioid carcinoma and inhibin , calretinin, WT-1 to show sex cord lineage (4,5,15,(17)(18)(19). Inhibin  and calretinin are highly sensitive and specific markers to show sex cord lineage, being expressed in 82% to 98% and 50% to 60% of ovarian pure Sertoli cell tumors (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is usually detected in granulosa cell tumours and other ovarian tumours and therefore not a useful marker for differentiation among them (Vang et al 2004;Riccardi et al 2007). Negative immunohistochemical reaction for desmin in this case is in accordance with the results of equal reactions, performed in other cases of granulosa cell tumours (Costa et al 1994).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In general, traditional immunohistochemical markers used for the distinction of epithelial, sex cord-stromal, and neuroendocrine tumors, such as pan-cytokeratin (pan-CK), low molecular weight cytokeratin (CK8/18), epithelial membrane antigen (EMA), inhibin, calretinin, CD99, synaptophysin, and chromogranin, can be useful; however, they may sometimes show overlapping patterns of expression. For example, Sertoli cell tumors can express epithelial markers such as cytokeratin (AE1/AE3 and CK8/18) in 38% to 100% of cases 11,13,21,22,37,49 whereas endometrioid carcinomas can express sex cord markers such as inhibin and calretinin in 0% to 25% and 0% to 36% of cases, respectively. 7,8,10,[14][15][16]19,20,25,[29][30][31][32]35,38,41,47,54 Although sex cord-stromal markers such as inhibin and calretinin have been extensively studied in ovarian sex cord-stromal tumors, most studies are predominantly composed of granulosa cell tumors.…”
mentioning
confidence: 99%
“…The number of Sertoli cell tumors that have been analyzed for various immunohistochemical markers in any given study is very small, and the majority of available immunohistochemical data are based on a mixture of pure Sertoli cell tumors, Sertoli-Leydig cell tumors, and mixed granulosa cell-Sertoli cell tumors (''gynandroblastoma'') from ovarian and testicular sites. 3,6,7,[11][12][13]17,19,[20][21][22]25,26,28,30,33,[35][36][37]38,44,47,49,51,53 Thus, a formal immunohistochemical comparison of ovarian pure Sertoli cell tumor, endometrioid tumors, and carcinoid tumor is lacking from the literature. Recently, a clinicopathologic study of 54 ovarian pure Sertoli cell tumors was reported, and immunohistochemical results for various markers were available in 23 cases; however, other tumors in the differential diagnosis were not evaluated because that was not the aim of that study.…”
mentioning
confidence: 99%
See 1 more Smart Citation